The Presidential Regime in the 1979 Constitution - Pareja Paz Soldán, José (1981)
A presidentialist regime is characterised by granting broad powers to the president of the Republic, who has a pre-eminent role in the running of the country. In this way, presidentialism conceives of the president as a key actor in the political orientation and public administration of the country, establishing a marked difference between legislative and judicial functions. In this context, the author discusses the advantages of this regime, focusing on the innovations introduced by the 1979 Magna Carta on this point. Thus, the author welcomes the fact that the constitutional text has created a neo-presidential system that visibly defines the functions of the executive and the legislature, promoting balance and collaboration between the two powers. Consequently, the author explores the central ideas of this regime, such as the control of the president by parliament, the prohibition of immediate re-election, presidential powers and the presidential veto.